How to reduce the impact of contaminated seafood on public health with the discharge of Fukushima nuclear wastewater - Bai, Yuntao; Yuan, Xiaolong; Wang, Lan (Frontiers in Sustainable Food Systems, 2023)
As wastewater from the Fukushima nuclear disaster continues to drain into the sea, the supply system for healthy seafood is being seriously challenged. In order to protect the health of the public, it is necessary to restructure the seafood supply mode. Seafood supply mode is divided into original mode, land farming and strengthen monitoring. In order to derive the applicable scope of various modes of seafood supply chain, and to provide recommendations for the safety and sustainability of seafood supply chains for governments and enterprises, three differential game models are constructed in this article. Then the equilibrium results obtained by the models are compared and analyzed. Finally, studies have shown that the health impact of seafood pollution is relatively small, and the government tends to choose the original supply mode. As the health impact of seafood grows, governments tend to prefer land-based farming. The social benefit to the government is directly proportional to the monitoring cost of seafood. In order to protect public health, enterprises tend to choose the mode of strengthening monitoring if the proportion of unqualified seafood is low. And if the sea products to the land environment of high degree of adaptation, they tend to choose land farming.